Real-Life Vancomycin Therapeutic Drug Monitoring in Coagulase-Negative Staphylococcal Bacteremia in Neonatal and Pediatric Intensive Care Unit: Are We Underestimating Augmented Renal Clearance? - Claudia Sette; Marcello Mariani; Luca Grasselli; Alessio Mesini; Carolina Saffioti; Chiara Russo; Roberto Bandettini; Andrea Moscatelli; Luca A. Ramenghi; Elio Castagnola (Antibiotics, 2023)
Bloodstream infections (BSI) from coagulase-negative-staphylococci (CoNS) are among the most frequent healthcare-related infections. Their treatment involves the use of vancomycin, a molecule whose optimal pharmacokinetic/pharmacodynamic (PK/PD) target for efficacy and safety is an area-under-curve/minimum inhibitory concentration (AUC/MIC) ratio ≥ 400 with AUC < 600. BSIs from CoNS in pediatric and neonatal intensive care unit that occurred at the Gaslini Institute over five years were evaluated to investigate the efficacy of vancomycin therapy in terms of achieving the desired PK/PD target and determining whether any variables interfere with the achievement of this target. AUC/MIC ≥ 400 with AUC < 600 at 48 and 72 h after therapy initiation was achieved in only 21% of the neonatal population and 25% of the pediatric population. In the pediatric population, an inverse correlation emerged between estimated glomerular filtration rate (eGFR) and achieved AUC levels. Median eGFR at 72 h was significantly higher (expression of hyperfiltration) in events with AUC < 400, compared with those with AUC ≥ 400 (p < 0.001). A cut-off value of eGFR in the first 72 h has been identified (145 mL/min/1.73 m2), beyond which it is extremely unlikely to achieve an AUC ≥ 400, and therefore a higher dose or a different antibiotic should be chosen.